Statyczna i dynamiczna ocena funkcjonalna wybranych parametrów stopy = Statistical and dynamical functional evaluation of the selected foot parameters - Srokowska, Anna; Foss, Jakub; Lewandowski, Andrzej; Siedlaczek, Marcin; Srokowski, Grzegorz; Radzimińska, Agnieszka; Weber-Rajek, Magdalena; Zukow, Walery (Journal of Education, Health and Sport, 2015)
Srokowska Anna, Foss Jakub, Lewandowski Andrzej, Siedlaczek Marcin, Srokowski Grzegorz, Radzimińska Agnieszka, Weber‑Rajek Magdalena, Zukow Walery. Statyczna i dynamiczna ocena funkcjonalna wybranych parametrów stopy = Statistical and dynamical functional evaluation of the selected foot parameters. Journal of Education, Health and Sport. 2015;5(7):568-589. ISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.44349 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%287%29%3A568-589 https://pbn.nauka.gov.pl/works/688281 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.06.2015. Revised 15.07.2015. Accepted: 25.07.2015. Statyczna i dynamiczna ocena funkcjonalna wybranych parametrów stopy Statistical and dynamical functional evaluation of the selected foot parameters 1Anna Srokowska, 1Jakub Foss, 1Andrzej Lewandowski, 2Marcin Siedlaczek, 2Grzegorz Srokowski, 2Agnieszka Radzimińska, 2Magdalena Weber‑Rajek, 3Walery Zukow 1 Katedra i Zakład Podstaw Kultury Fizycznej UMK w Toruniu Collegium Medicum im. L. Rydygiera w Bydgoszczy 2 Katedra Fizjoterapii, Zakład Kinezyterapii i Masażu Leczniczego UMK w Toruniu Collegium Medicum im. L. Rydygiera w Bydgoszczy 3 Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy Adres do korespondencji: 1. mgr Anna Srokowska, Katedra i Zakład Podstaw Kultury Fizycznej UMK w Toruniu Collegium Medicum im. L. Rydygiera w Bydgoszczy, ul. Świętojańska 20, 85-077 Bydgoszcz, tel. 600341155, e-mail a.srokowska@cm.umk.pl 2. dr Grzegorz Srokowski, Katedra Fizjoterapii, Zakład Kinezyterapii i Masażu Leczniczego UMK w Toruniu Collegium Medicum im. L. Rydygiera w Bydgoszczy, ul. Techników 3, 85-801 Bydgoszcz, tel. 608591155, e-mail g.srokowski@gmail.com Słowa kluczowe: stopa, diagnoza, badanie statyczne, badanie dynamiczne. Streszczenie Praca dotyczyła porównania metod badania statycznego i dynamicznego dla oceny funkcjonalnej stopy. Badanie przeprowadzone zostało w grupie 22 przedszkolaków z jednego z bydgoskich przedszkoli. Grupę stanowiło 11 dziewcząt i 11 chłopców w wieku 6-7 lat. Pomiary statyczne wykonane zostały na podstawie zdjęć z podoskopu, pomiary dynamiczne na obrazach pozyskanych z programu komputerowego z podłączoną platformą tensometryczną. Do badania w obu metodach wykorzystano te same parametry: długość stopy, szerokość stopy, kąt koślawienia palucha, kąt szpotawienia palca V, kąt piętowy, kąt Clarke’a, wskaźnik Ky oraz wskaźnik Wejsfloga. Pomiary wykonywane były przy pomocy programów komputerowych. Wyniki uzyskane w toku badań statycznych i dynamicznych różnią się od siebie. Największą zmianę procentową zaobserwowano w zmianie wartości kąta α stopy lewej u chłopców, najmniejsze różnice we wskaźniku „W”. Badaniem lepiej odwzorowującym stan czynnościowy stopy jako organu amortyzacyjnego było badanie dynamiczne. Jednakże badanie statyczne stopy jest również wystarczającym narzędziem do przeprowadzenia pełnowartościowej diagnozy. Keywords: foot, diagnosis, static examination, dynamic examination. Abstract The work involved a comparison of methods of static and dynamic tests for assessing functional foot. The examination was conducted in a group of 22 preschoolers from one of Bydgoszcz kindergartens. Group consisted of 11 girls and 11 boys aged 6-7 years. Static measurements were made on the basis of photographs of podoscope, dynamic measurements on the images obtained from a computer program connected strain gauge platform. The same parameters were used in both methods, and included: length, width, alpha angle, beta angle, gamma angle, Clarke angle, Ky index, Wejsflog index. Measurements were made while using a computer programme. The results obtained in the course of static and dynamic tests differ from each other. The biggest percentage change was observed in the change of angle α left foot in boys, the smallest differences in the rate of "W". The study better mapping from the functional status of the foot as a body amortization was dynamic test. However, the static test of the foot is also sufficient tool to conduct full-fledged diagnosis.